2022
DOI: 10.1177/20551029221121524
|View full text |Cite
|
Sign up to set email alerts
|

Men’s experiences of alopecia areata: A qualitative study

Abstract: Alopecia areata (AA) affects men at similar rates to women, yet comparatively little is known about men’s experience of the condition. We interviewed a demographically diverse group of 18 men with AA to explore this gap. From qualitative thematic analysis, participants’ accounts described a profound yet often-minimised impact of AA on their lives, in the context of poor public awareness and misguided assumptions about AA in men. Conversely, this adversity appeared to facilitate personal growth for many. These … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
9
0
Order By: Relevance
“…Feelings of sadness, insecurity, inadequacy, and selfconsciousness (8), as well as feelings of depression, anxiety, and suicidal thoughts (7) were prevalent. The majority of qualitative research highlights that people struggle with everyday activities, such as participating in sports or social events, due to a fear of their appearance being noticed (7)(8)(9). The unpredictable nature of AA was also highlighted as a source of distress in particular (7,8) and women seem to report more stress and distress than men (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…Feelings of sadness, insecurity, inadequacy, and selfconsciousness (8), as well as feelings of depression, anxiety, and suicidal thoughts (7) were prevalent. The majority of qualitative research highlights that people struggle with everyday activities, such as participating in sports or social events, due to a fear of their appearance being noticed (7)(8)(9). The unpredictable nature of AA was also highlighted as a source of distress in particular (7,8) and women seem to report more stress and distress than men (10,11).…”
Section: Introductionmentioning
confidence: 99%
“…It also emerged consistently across subgroups, although among males, it was not one of the most frequently cited. As suggested by Zuchelli et al (2022) 2017). Although many individuals report greater social satisfaction because of cosmetic strategies (Park et al, 2018), in the present study, some reported that use hindered their acceptance of AA and only served as a "social buffer," suggesting that use might curb one's adjustment and comfort within social contexts.…”
Section: Active Copingmentioning
confidence: 79%
“…It also emerged consistently across subgroups, although among males, it was not one of the most frequently cited. As suggested by Zuchelli et al (2022), this may be due to social stigmas and gendered marketing associated with hairpiece use. Regardless, such coping strategies are frequently noted in the existing literature, particularly among women (e.g., Matzer et al, 2011; Montgomery et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Strategies for managing AA may also differ by gender, with men who have AA noting sociocultural barriers to using many aesthetic products like wigs. 11 Despite most of these products and services also incurring monetary costs, no research has quantified their direct financial cost. Recent case-control research established the notable indirect costs of AA via elevated rates of mental health service use, diagnoses of common mental health conditions, absenteeism and unemployment in affected individuals compared to controls.…”
Section: Introductionmentioning
confidence: 99%